The Impact of Electric Power Industry Reform Act (EPIRA) on the Philippine Power Sector: A Thematic Literature Review - Macalanos, Jr., Celso; Aloba, Jerian; Abangan, Aileen (JPAIR Multidisciplinary Research, 2026)
The Electric Power Industry Reform Act (EPIRA) of 2001 was enacted to transform the Philippine energy landscape from a state-owned monopoly into a competitive, market-driven industry. This study presents a thematic literature review assessing the multifaceted impacts of EPIRA over two decades of implementation. Synthesizing academic research, policy papers, and institutional reports, the review identifies five critical themes: (1) the unbundling of the power sector and its influence on operational efficiency; (2) the paradox of electricity pricing, where market competition has struggled to lower costs for residential consumers; (3) the technical and financial performance of Electric Cooperatives (ECs) compared to private distribution utilities; (4) the persistent challenges of rural electrification and energy security in off-grid areas; and (5) the broader economic consequences of high electricity prices. Methodologically, the study employs a qualitative systematic review with thematic synthesis, ensuring transparency and rigor. Findings suggest that while EPIRA reduced the government’s fiscal burden and improved technical efficiency in some sectors, it has faced significant criticism regarding high power rates, regulatory capture, and policy misalignment with renewable energy goals. This review provides a foundation for future legislative amendments aimed at achieving more equitable energy distribution, consumer-focused pricing, and sustainable energy transition.